Investigation of hygroscopic properties of the spelt grain - Stankevych, Georgii; Kats, Anfisa; Vasyliev, Serhii (Technology audit and production reserves, 2018)
The object of research is the hygroscopic properties of the not collapsed (with flower films) and the collapsed (with the removed films) spelt grains. One of the problems is that during post-harvest processing and storage of spelt grain in different environmental conditions, its moisture can occur, which can lead to deterioration in the quality of the harvested crop. To prevent this, it is necessary to know the hygroscopic properties of spelt, in particular its equilibrium moisture, depending on the parameters of the air – its temperature and relative humidity. It is promising to predict the equilibrium moisture content of spelt according to the conditions of its processing or storage, which will avoid undesirable consequences. For the study of the hygroscopic properties of not collapsed and collapsed spelt, a common tensometric method for determining the equilibrium moisture is used. The experiments are carried out in the range of air temperatures of 5...25 °C and its relative humidity of 33...70 %, simulating the conditions of active ventilation and storage of grain at different times of the year. The numerical values of the equilibrium moisture content of spelt of variety Zorya Ukrainy of 2016 harvest are obtained for the indicated temperature ranges and relative air humidity. The equilibrium humidity of not collapsed spelt (in flower films) is within 9.35...13.78 %, collapsed (without films) – within 9.98...14.58 %. Compared with not collapsed spelt, the equilibrium moisture content of the collapsed is higher by 0.42...0.74 %, which must be taken into account when storing the latter. The nature of the dependence of the equilibrium humidity of not collapsed and collapsed spelt on the parameters of the ambient air – temperature and relative humidity is established. An empirical equation is proposed that allows predicting the values of the equilibrium moisture content of spelt depending on environmental parameters. This allows to justify the rational modes of post-harvest processing of spelt, especially active ventilation, predict safe storage periods depending on environmental conditions and prevent a decline in grain quality indicators.